PTH-228 Genotyping of rotavirus isolates prior to the introduction of the rotavirus vaccine in scotland and early indications of the impact of the vaccine. (22nd June 2015) - Mukhopadhya, I; Berry, S; Hunt, A; Murdoch, H; Smith-Palmer, A; Hold, GL
Abstract : Introduction: Rotaviruses (RV) are the leading cause of severe gastroenteritis in children less than five years of age worldwide. Rotarix®, a live attenuated monovalent vaccine containing a RV strain of G1P[8] specificity has been included in the routine childhood immunisation schedule from June 2013 in Scotland and is offered to infants under the age of four months in two doses. This study aimed to characterise the prevalent rotavirus strains in Scotland prior to the introduction of the vaccine. Method: Rotavirus positive faecal samples from various Scottish regional virology laboratories covering the years 2012–2013, before the introduction of the vaccine, were genotyped. Viral RNA was extracted from faecal suspensions using guanidine isothiocyanate – silica gel extraction method. VP7 and VP4 gene specific multiplex hemi-nested PCRs were used for genotyping. Surveillance systems were established by Health Protection Scotland to monitor the impact of the vaccine. Results: A total of 387 samples were genotyped from the regional virology laboratories in Aberdeen, Dundee, Inverness, Glasgow and Edinburgh. The commonest strain in Scotland was G1P[8] accounting for 72.1% of cases. The other strains that were identified were G2P[4] in 7.2%, G4P[8] in 6.9%, G9P[8] in 3.4% and G3P[8] in a further 2.3% of cases. Single cases of G12P[8] and G9P[4] were also found (0.26% respectively). Mixed infections were seen in 5.4% of cases. The provisional uptake for the first dose of Rotarix® vaccine in Scotland for children born between 1 st of July to 30 th Sept 2013 was 92.7%% for the completed course by 12 months. The laboratory confirmed cases of RV reported to HPS via ECOSS (The Electronic Communication of Surveillance in Scotland) showed a marked reduction in confirmed reports of RV compared to a three year average of the years 2011–13. Surrogate markers, e.g. calls to NHS24 and GP consultations with childhood diarrhoea and vomiting, have also shown a downward trend. Conclusion: The pre-vaccine surveillance of RV strains confirms that G1P[8] is the predominant strain in Scotland. There has been a promising reduction in laboratory confirmed cases of RV in Scotland following the introduction of the vaccine. The baseline genotyping data will be used to ascertain cross protection against strains and also identify vaccine induced RV strain shifts and an overall evaluation of the programme. Disclosure of interest: None Declared.